From Societeit De Harmonie to the Gedung Rakyat Indonesia: The Transformation of a Building’s Function in Semarang, 1906–1990 - Aynun Aska Abdillah; Eka Yudha Wibowo (Historia, 2027)
This study examines the history and developmental dynamics of Societeit De Harmonie in Semarang from 1906 to 1990. The primary focus of this study is to analyze the transformation of the building’s function and significance from the colonial era through the post-independence period, specifically when it became the Gedung Rakyat Indonesia Semarang (GRIS). This study employs historical methods, specifically heuristics, verification, interpretation, and historiography, utilizing primary sources such as colonial newspapers accessed via Delpher and national newspapers like Suara Merdeka. The findings reveal that Societeit De Harmonie served as a symbol of exclusivity within the European community and reflected social stratification during the colonial era. In the post-independence era, ownership and function shifted from a private building to a public one that the community could use. Over time, the GRIS building declined due to management conflicts, policy changes, and waning public interest.